Sucrose interferes with endogenous cytokinin homeostasis and expression of organogenesis-related genes during de novo shoot organogenesis in kohlrabi - Ćosić, Tatjana; Motyka, Václav; Savić, Jelena; Raspor, Martin; Marković, Marija; Dobrev, Petre I; Ninković, Slavica (Scientific reports, 2021)
Cross-talk between phytohormones and sugars is intensely involved in plant metabolism, growth and regeneration. We documented alterations in cytokinin (CK) homeostasis in four developmental stages during de novo shoot organogenesis (DNSO) of kohlrabi (Brassica oleracea var. gongylodes cv. Vienna Purple) seedlings induced by exogenous CKs, trans-zeatin (transZ) and thidiazuron (TDZ), added together with elevated sucrose concentration (6% and 9%). Significant impact of CK and sucrose treatment and their interaction was recorded in all investigated stages, including plantlet development before calli formation (T1 and T2), calli formation (T3) and shoot regeneration (T4). Results showed remarkable increase in total CK levels for transZ treatment, particularly with 9% sucrose. This trend was observed for all physiological and structural groups of CKs. Application of TDZ contributed to little or no increase in CK levels regardless of sucrose concentration. Analysis of expression profiles of organogenesis-related genes involved in auxin transport, CK response, shoot apical meristem formation and cell division revealed that higher sugar concentration significantly downregulated the analysed genes, particularly in T3. This continued on TDZ, but transZ induced an opposite effect with 9% sucrose in T4, increasing gene activity. Our results demonstrated that phytohormone metabolism might be triggered by sucrose signalling in kohlrabi DNSO.
Keywords: thiadiazoly; Thiadiazoles; Plant Growth Regulators; Zeatin; sacharosa; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Phenylurea Compounds; rostlinné geny; regulátory růstu rostlin; Genes, Plant; homeostáza; Homeostasis; Brassica; Sucrose; fenylmočovinové sloučeniny; zeatin; meristém; Meristem